Vertical transmission of fungal endophytes is widespread in forbs - Hodgson, Susan (Blackwell Publishing Inc, 2014)
To date, it has been thought that endophytic fungi in forbs infect the leaves of their hosts most commonly by air-borne spores (termed “horizontal transmission”). Here, we show that vertical transmission from mother plant to offspring, via seeds, occurs in six forb species (Centaurea cyanus, C. nigra,Papaver rhoeas,Plantago lanceolata,Rumex acetosa, and Senecio vulgaris), suggesting that this may be a widespread phenomenon. Mature seeds were collected from field-grown plants and endophytes isolated from these, and from subsequent cotyledons and true leaves of seedlings, grown in sterile conditions. Most seeds contain one species of fungus, although the identity of the endophyte differs between plant species. Strong evidence for vertical transmission was found for two endophyte species, Alternaria alternata and Cladosporium sphaerospermum. These fungi were recovered from within seeds, cotyledons, and true leaves, although the plant species they were associated with differed. Vertical transmission appears to be an imperfect process, and germination seems to present a bottleneck for fungal growth. We also found that A. alternata and C. sphaerospermum occur on, and within pollen grains, showing that endophyte transmission can be both within and between plant generations. Fungal growth with the pollen tube is likely to be the way in which endophytes enter the developing seed. The fact that true vertical transmission seems common suggests a more mutualistic association between these fungi and their hosts than has previously been thought, and possession of endophytes by seedling plants could have far-reaching ecological consequences. Seedlings may have different growth rates and be better protected against herbivores and pathogens, dependent on the fungi that were present in the mother plant. This would represent a novel case of trans-generational resistance in plants.